2010
DOI: 10.1111/j.1532-849x.2009.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Education in Prosthodontics: Residents’ Perspectives on Their Current Training and Future Goals

Abstract: This is the first report identifying current prosthodontic residents' demographics and their perspectives on their clinical training and future goals. Several trends were identified, indicating a bright future for the specialty. By knowing the students' perceptions regarding their training and future goals, the American College of Prosthodontists and/or program directors will be able to use this information to improve residency programs and the specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The study was performed using data from a previously published study, representing approximately 48% of all prosthodontic residents in the United States 16 . Data regarding FTDs in AEP programs were retrieved from the American Dental Association (ADA) 9 .…”
Section: Methodsmentioning
confidence: 99%
“…The study was performed using data from a previously published study, representing approximately 48% of all prosthodontic residents in the United States 16 . Data regarding FTDs in AEP programs were retrieved from the American Dental Association (ADA) 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have sought to determine why prosthodontic residents choose specific programs 9 14 . Reasons for choosing prosthodontics as a specialty have been found to include complexity and challenge of treatment planning and execution of treatment, 9 clinical education, 10 faculty influence or mentoring, 9 , 11 length of program, 11 cost, 11 , 13 , 14 and program location 14 . A recent survey examining maxillofacial prosthodontists’ rationale for pursuing maxillofacial prosthetic training found the main reasons were personal satisfaction, mentorship, and prosthodontic residency exposure 15 …”
Section: Accredited Programs In Maxillofacial Prosthetics 2018mentioning
confidence: 99%
“…Blissett et al 14 recently demonstrated that junior residents in AEP programs put a higher value on placing implants than did their senior classmates, suggesting that implant placement is an important factor to junior residents. A more recent study also showed the majority of AEP residents reported they had adequate knowledge in basic didactic and clinical dental implant prosthodontics; 15 however, the authors did not investigate the residents’ perspectives on their comprehensive implant training.…”
mentioning
confidence: 95%